Chroman‐4‐one‐Based Amino Bidentate Ligand: An Efficient Ligand for Suzuki‐Miyaura and Mizoroki‐Heck Coupling Reactions in Aqueous Medium. Issue 35 (15th September 2021) - Khan, Danish; Parveen, Iram
Abstract: A new family of phosphine‐free Amino‐chroman‐4‐one ((Z)‐2‐ethoxy‐3‐((phenylamino)methylene)chroman‐4‐one) bidentate ligands ware successfully synthesised and characterised. The bidentate ligand act as efficient catalyst with combination of Pd (II) salt in the C−C bond formation and exhibited excellent performance in the Suzuki‐Miyaura and Mizoroki‐Heck coupling reaction. A broad range of substrates, including heterocyclic, flavones, Isatin and sterically hindered coupling partner, were well tolerated under the optimized reaction conditions. Metal complex and all the intermediates were formed in the catalytic cycle were characterized by mass spectrometry to support the reaction mechanism. Abstract : A new family of phosphine‐free, air and moisture stable ligand are developed for coupling reaction. The synthesised ligand efficiently catalyzed the coupling reaction with PdCl2. The main advantage of the developed protocol is the tolerance of wide substrate including sterically hindered substrates, low ligand loading and short reaction time with good‐to‐excellent yield.